Women and politics: the contestation for visibility - Kartini Aboo Talib @ Khalid,; Nurul Asmaa Ramli,; Chan, Rachel Suet Kay; Zaireeni Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The history of voting in the West peppered with women’s struggles to achieve a voice in politics. Gender and elections in a democratic system vary according to context. Still, gender equality and equity for women have always required the government’s intervention. The feasible way to empower women and to ensure gender sensitivity has been to enforce rules and regulations. Nevertheless, women’s political participation in Malaysia is still low due to power distances between genders resulting from a patriarchal system. However, we have to look beyond just numbers to assess the impact of women on politics. This article argues that though the number of female political representatives is low, their visibility should also be gauged from their behind-the-scenes contribution as party members. This study was drawn from the election campaign in 2018 using non-participant observation and secondary data to challenge the prevailing Western approach to gender studies. The findings show that some of the factors mentioned above are not necessarily the reasons for the sluggish appearance of women’s participation in politics.